Vocabulary Strategies for English Learners - Sutisno Adam; Sulmi Magfirah (Hasanuddin University, 2022)
Vocabulary is an essential part of a language. In Indonesia, especially in Ternate, many students struggle to enrich their vocabulary on mastering English. Students find difficulties in learning English and strategies in learning vocabulary. Therefore, this study aims to investigates vocabulary strategies for English learners. The research purposes were: 1) to determine the students' strategies in learning vocabulary and 2) to determine the dominant strategies used by university students. In this study, the researcher used a descriptive qualitative design, and the subjects of the study were students of Khairun University, consisting of 59 students. The data of the study were collected through a questionnaire. The result found that students used all types of vocabulary learning strategies. However, they used the memory and cognitive learning strategy more often than other strategies. Additionally, using a dictionary, repeatedly spelling the word in mind, and consciously contacting the target language through various media were the dominant strategies used by the students.